Gerenciamento do cuidado : ações dos enfermeiros em um serviço hospitalar de emergência - Santos, José Luis Guedes dos (2011)
This study aimed to analyze care management actions performed by nurses in a hospital emergency service. This is a qualiative research of the case study type, carried out with nurses from the Emergency Service of a University Hospital in southern Brazil. The data were collected through participant observation and semi-structured interviews, and analyzed using thematic analysis. The results show nurses’ actions in care planning, forecasting and provisioning of resources, supervision, leadership and training of the nursing team. In care planning, there is the execution of the nursing process and the control of the realization of laboratory and radiological tests. The actions of forecasting and provisioning of resources were: elaboration of the monthly schedule of employees, daily distribution of the staff and the management of material resources. Leadership encourages the planning of care, the coordination of the nursing staff and the delegation of activities.